La valutazione dei costi: uno studio applicato all’unità operativa di diagnostica per immagini - Nieddu, Salvatore; Bianco, Maurizio (Farmeconomia. Health economics and therapeutic pathways, 2001)
The aim of the analysis was to evaluate the reasons that caused the poor economic results and performances of a Radiology Department located in a public hospital. The models of Decision Support System were utilized in order to conduct the studies. These models represent clearly a current economic situation and allow simulations in order to estimate in a preventive way the economic results of different alternative actions. The economic analysis was conducted according to the extended direct costing method utilizing a single performance (product) as a calculation unit. The simulations were carried out in accordance to the “price-cost-volume analysis” method that identifies the break even point for the families of products. These analysis resulted in a significant improvement of the awareness relative to the economic actions of the operative managerial decisions: the main factor in the process of the decision making for the public healthcare structure is to respond to the needs of the potential users and therefore to satisfy the demand, the increase of which is immediately signalised by the lengthening of the awaiting list. For the structure which is incorporated in the hospital frame there is the necessity to provide the service towards inside the hospital both relative to the patients and to the performances of first aid supported by the emergency department. It is important to stress that, even if limited or conditional, there is a space for improvement: the first step in this direction is to analyse in order to recognize and to measure, if not able to improve that what is unknown and not measured before.